1997
DOI: 10.1007/bf00879659
|View full text |Cite
|
Sign up to set email alerts
|

Indium-111 pentetreotide single-photon emission tomography in patients with TSH-secreting pituitary adenomas: Correlation with the effect of a single administration of octreotide on serum TSH levels

Abstract: Few data are available on the visualization of somatostatin receptors in vivo in patients with thyrotropin (TSH)-secreting adenoma. We studied five patients with TSH-secreting adenomas using single-photon emission tomography (SPET) after administration of indium-111 pentetreotide. The intensity of 111In-pentetreotide uptake by the tumours was correlated with the degree of TSH suppression after a single administration of 100 microg octreotide s. c. Five patients (three women and two men) aged 27-46 years were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…Two authors studied uptake of 111 In-pentreotide, a scintigraphic marker of somatostatin receptors. 16,17 Losa et al evaluated 5 TSH-secreting PAs and observed a corresponding decrease in 111 In-pentreotide uptake and serum TSH levels in the PAs following a dose of octreotide, though the trend was not statistically significant. Yonekura et al additionally observed that positive 123 I-epidepride uptake was an indirect marker of D2 receptors and was therefore valuable for diagnosis and treatment planning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two authors studied uptake of 111 In-pentreotide, a scintigraphic marker of somatostatin receptors. 16,17 Losa et al evaluated 5 TSH-secreting PAs and observed a corresponding decrease in 111 In-pentreotide uptake and serum TSH levels in the PAs following a dose of octreotide, though the trend was not statistically significant. Yonekura et al additionally observed that positive 123 I-epidepride uptake was an indirect marker of D2 receptors and was therefore valuable for diagnosis and treatment planning.…”
Section: Resultsmentioning
confidence: 99%
“…GH-secreting PAs cause acromegaly and are responsive to octreotide, a somatostatin analog; however, GH levels normalize in only 30–45% of patients following medical treatment. 12 Thyrotropin (TSH)-secreting adenomas account for 1% of all PAs and are often misdiagnosed as Graves’ disease; 16 as a result, tumors tend to be larger and more invasive when finally discovered, rendering surgical removal difficult. 16,32,33 Eradication of functional residual following surgery is only achieved in about 40% of TSH-secreting PAs, even after adjunctive radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between the increased 111 Inpentetreotide uptake in TSH-secreting pituitary adenomas and the inhibition of excessive TSH secretion by octreotide has also been shown [22,[33][34][35]. 111 Inpentetreotide scintigraphy was negative in patients with microprolactinomas and ACTH-secreting pituitary microadenomas [26].…”
Section: Somatostatin Receptor Scintigraphymentioning
confidence: 92%
“…Similarly, a positive correlation between the increased 111 In-pentetreotide uptake in TSH-secreting pituitary adenomas and the inhibition of excessive TSH secretion by octreotide has been shown [35,38]. 111 In-pentetreotide scintigraphy was negative in patients with microprolactinomas and ACTH-secreting pituitary microadenomas [37,39].…”
Section: Somatostatin Receptor Imaging Of Pituitary Tumorsmentioning
confidence: 94%